Extending the half-life of a fab fragment through generation of a humanized anti-human serum albumin Fv domain: An investigation into the correlation between affinity and serum half-life. Issue 7 (2nd October 2016) - Adams, Ralph; Griffin, Laura; Compson, Joanne E.; Jairaj, Mark; Baker, Terry; Ceska, Tom; West, Shauna; Zaccheo, Oliver; Davé, Emma; Lawson, Alastair DG.; Humphreys, David P.; Heywood, Sam
ABSTRACT: We generated an anti-albumin antibody, CA645, to link its Fv domain to an antigen-binding fragment (Fab), thereby extending the serum half-life of the Fab. CA645 was demonstrated to bind human, cynomolgus, and mouse serum albumin with similar affinity (1–7 nM), and to bind human serum albumin (HSA) when it is in complex with common known ligands. Importantly for half-life extension, CA645 binds HSA with similar affinity within the physiologically relevant range of pH 5.0 – pH 7.4, and does not have a deleterious effect on the binding of HSA to neonatal Fc receptor (FcRn). A crystal structure of humanized CA645 Fab in complex with HSA was solved and showed that CA645 Fab binds to domain II of HSA. Superimposition with the crystal structure of FcRn bound to HSA confirmed that CA645 does not block HSA binding to FcRn. In mice, the serum half-life of humanized CA645 Fab is 84.2 h. This is a significant extension in comparison with < 1 h for a non-HSA binding CA645 Fab variant. The Fab-HSA structure was used to design a series of mutants with reduced affinity to investigate the correlation between the affinity for albumin and serum half-life. Reduction in the affinity for MSA by 144-fold from 2.2 nM to 316 nM had no effect on serum half-life. Strikingly, despite a reduction in affinity to 62 µM, an extension in serum half-life of 26.4 h was still obtained. CA645 Fab and the CA645 Fab-HSA complex have been deposited in the Protein Data Bank (PDB) with accession codes, 5FUZ and 5FUO, respectively.